2007
DOI: 10.1007/s11832-007-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of thoracic kyphosis and lumbar lordosis during growth

Abstract: Purpose The aim of this study was to establish ranges of angular variation in lordotic and kyphotic curves in normal male and female children and adolescents. Methods We developed a pantograph to measure dorsal curves. It consisted of a tripod-supported vertical strut to which an articulated bar was fixed and which had an arm that was able to follow the dorsal surface while moving up and down. This arm was positioned over the C7 spinous process and followed spinous processes to L5 at constant speed. A laser be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 21 publications
2
44
2
6
Order By: Relevance
“…Thus far, no data has been published which has attempted to identify environmental factors, such as the geographical locality, which may significantly affect the size and distribution of the different postural parameters. Some authors have already shown that a decrease in the lumbar lordosis angle size is positively correlated with the age of an individual [3,8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus far, no data has been published which has attempted to identify environmental factors, such as the geographical locality, which may significantly affect the size and distribution of the different postural parameters. Some authors have already shown that a decrease in the lumbar lordosis angle size is positively correlated with the age of an individual [3,8].…”
Section: Discussionmentioning
confidence: 98%
“…Cil et al and Giglio and Volpon examined the postural characteristics of a population of children and young people aged between 5 and 20 years. The scientists showed that the angle of lumbar lordosis increased with age [3,8]. Willner and Johnson also examined a group of 1101 children aged between 8 and 16 years [20].…”
Section: Discussionmentioning
confidence: 99%
“…Zmienność postawy ciała i związane z tym zmiany wychyleń przednio-tylnych kręgosłupa są wpisane w ontogenezę [9,22,23]. Z opinią o spłaszczaniu się lordozy wraz z wiekiem, co miałoby powodować zmiany degeneracyjne, nie wszyscy badacze się zgadzają [24,25], a jeszcze inni sugerują nawet jej zwiększanie [26].…”
Section: Omówienieunclassified
“…We know to what criteria a good or optimal curvature in the spine should meet. Semi recent literature on good postures is very scarce and not informative what the found variation in (mostly radiologic) measurements of curvature means [23][24][25]. The variation in curvature in early adulthood should be seen as a resultant of all growing processes and not as a given starting point or genetically desired endpoint.…”
Section: How Does This Disproportionate Growth Work Out At the Level mentioning
confidence: 99%